Efficacy of dexamethasone as an adjuvant to bupivacaine in supraclavicular brachial plexus block - Vaidya, Sagun Ram; Neupane, Sandeep; Shrestha, Kundu; Ghale, Tumaya (Journal of Gandaki Medical College-Nepal, 2022)
Introduction: Supraclavicular brachial plexus block provides the optimal operating conditions for upper arm surgery. The study was conducted to assess the efficacy of dexamethasone as an adjuvant to bupivacaine in supraclavicular brachial plexus block. Methods: An experimental study was performed in Gandaki Medical College and Teaching hospital, Pokhara. Forty patients undergoing surgery of the elbow, forearm, and hand under supraclavicular brachial plexus block, with 0.25% bupivacaine with normal saline (n = 20) in the Group I versus 0.25% bupivacaine with dexamethasone (n = 20) in Group II with an equal volume of 30 ml in each group. Randomization was done and the onset of sensory and motor blockade and duration of analgesia was compared in both groups. Statistical package for the social sciences version 24.0 software was used. Continuous variables like the onset of sensory and motor block and time to first rescue analgesia were assessed with the student’s t-test and the chi-square test was applied to assess categorical variables like visual analogue score score. Results: The time to onset of sensory block in the bupivacaine only group was 504.10±70.24 seconds compared to bupivacaine with dexamethasone group (255.65±75.28) seconds. The time to onset of motor block in the bupivacaine-only group was 813.00±74.57 seconds compared to bupivacaine with dexamethasone group (524.25±80.38) seconds. Time to first rescue analgesia in bupivacaine only group was 542.5±126.33 minutes compared to bupivacaine with dexamethasone group (1245±325.66) minutes. The difference was statistically significant in all the findings (p<0.0001). Conclusions: The study concluded that the addition of dexamethasone to bupivacaine prolongs the duration of analgesia and provides faster onset of sensory and motor blocks.